1994
DOI: 10.1080/00071669408417734
|View full text |Cite
|
Sign up to set email alerts
|

Weight of internal organs and carcase yield of early food restricted broilers

Abstract: 1. Effects of food restriction on growth rate and relative growth rates of supply organs (liver, heart, lungs and kidneys, digestive tract) and demand organs (breast, back, thighs, abdominal fat) of broiler chickens were studied. 2. Birds were restricted in intake to 50% (group FI 50) or 75% (group FI 75) of ad libitum from 5 to 11 d of age; all birds were fed ad libitum from 12 to 39 d of age. 3. Relative growth rates from 12 to 39 d of age of group FI 50 were higher (P < 0.05) than group FI 75 and control gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
15
3
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 24 publications
10
15
3
1
Order By: Relevance
“…It is suggested that, though fenugreek has negative effects on growth in general, the growth of the intestine has not been retarded. The findings of Govaerts et al (2000) and Susbilla et al (1994) that growth of supply organs such as stomach and intestine receives priority in nutrient partitioning within the body support the above hypothesis. Meanwhile, the relative weight of the pancreas of the birds fed 5% dietary fenugreek was significantly higher than other groups.…”
Section: Table 2 Effects Of Dietary Fenugreek Powder On Growth Perfosupporting
confidence: 68%
“…It is suggested that, though fenugreek has negative effects on growth in general, the growth of the intestine has not been retarded. The findings of Govaerts et al (2000) and Susbilla et al (1994) that growth of supply organs such as stomach and intestine receives priority in nutrient partitioning within the body support the above hypothesis. Meanwhile, the relative weight of the pancreas of the birds fed 5% dietary fenugreek was significantly higher than other groups.…”
Section: Table 2 Effects Of Dietary Fenugreek Powder On Growth Perfosupporting
confidence: 68%
“…The breast muscle yield was lower in feed-restricted birds at the end of restriction, while at the end of realimentation the breast muscle yield was comparable among previously feed-restricted and birds fed ad libitum (Zhan et al 2007). However, no differences in breast meat yield were observed between birds fed restricted diets (50% of ad libitum intake) and ad libitum diet from days 5 to 11 and had free access to feed from days 12Á39 (Susbilla et al 1994). In line with the findings of our study, Santoso et al (1995) noticed less abdominal fat in broiler chickens subjected to severe early feed restriction.…”
Section: Discussionsupporting
confidence: 81%
“…During restriction, due to a reduction in feed quality, this lower nutritional condition caused reduction in the size of visceral organs and this might be due to the smaller amount of energy and protein available for development (Sainz and Bentley 1997). During realimentation, when the restricted birds are fed a higherquality diet, the organs previously having slower growth and size will compensate for their early slower development (Susbilla et al 1994;Zubair and Lesson 1994). These results indicate that early nutrient restriction, especially lysine restriction, affects the development of visceral organs and hence the growth performance of birds and that on removal of the nutrient restriction, birds compensate for the growth and development of visceral organs and this is reflected in the greater weight gain of the birds.…”
Section: Discussionmentioning
confidence: 99%
“…Gonzales et al (1998) mostraram que frangos foram capazes de apresentar ganho compensatório após o período de restrição alimentar realizada entre o oitavo e o décimo quarto dias de idade. Resultados semelhantes foram encontrados por Susbilla et al (1994). Entretanto, Yu et al (1990) e não observaram ganho compensatório, após um período de restrição alimentar, sugerindo que o mesmo não existe.…”
Section: Introductionunclassified